Left and Right Censoring for Expected Time to Seroconversion – A Shock Model Approach - K. Kannadasan, R. Rajivgandhi, A. Ganesan, R. Vinoth (Recent Research in Science and Technology, 2010)
The time to cross-antigenic threshold of the infected personÃ¢â‚¬â„¢s is a vital event. Once the accumulated number of events exists from the persons which as a certain threshold level, it could be viewed as a Ã¢â‚¬Å“Break down pointÃ¢â‚¬Â. The important characteristic for the antigenic diversity threshold for a person is the time to attain the break down point. In this paper, a shock model approach is proposed to obtain the expectation time to attain the threshold level. Attempt to find patients censoring value is also seen. Graphical illustrations are provided for the use of the model.